2022
DOI: 10.1155/2022/7690960
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypoxic Environment on Periodontal Tissue through the ROS/TXNIP/NLRP3 Inflammasome Pathway

Abstract: There is low evidence for the possible association between obstructive sleep apnea-hypopnea syndrome (OSAHS) and periodontitis, necessitating further research. This study was aimed at investigating this association. For the in vitro study, 8-day-old Wistar rats were divided into the unilateral nasal obstruction group (UNO) and the sham surgery group (SHAM). Rats in the former group were subjected to UNO by cauterization of the external nostril at the age of 8 days. Immunofluorescence analysis, quantitative rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Hypoxia also stimulates pro-inflammatory cytokine production, including interleukin (IL)-1b and matrix metalloproteinase 8 (MMP-8). 74,75 Additionally, some researchers posit that the periodontal pocket is an acidic microenvironment (even opH 5), which arises due to dental plaque and inflammatory cells. 13,76,77 As for the temperature of the periodontal pocket, it is close to body temperature; however, periodontitis patients have higher temperatures when compared with healthy individuals.…”
Section: The Hydrogel Stimuli-responsive Methodsmentioning
confidence: 99%
“…Hypoxia also stimulates pro-inflammatory cytokine production, including interleukin (IL)-1b and matrix metalloproteinase 8 (MMP-8). 74,75 Additionally, some researchers posit that the periodontal pocket is an acidic microenvironment (even opH 5), which arises due to dental plaque and inflammatory cells. 13,76,77 As for the temperature of the periodontal pocket, it is close to body temperature; however, periodontitis patients have higher temperatures when compared with healthy individuals.…”
Section: The Hydrogel Stimuli-responsive Methodsmentioning
confidence: 99%
“…Insufficient oxygen supply interferes with cellular metabolism, resulting in cell death. Hypoxia can induce the excessive production and accumulation of ROS in HPDLCs and induce inflammatory response, damaging periodontal tissues (Zhu et al, 2022).…”
Section: Effect Of Hypoxia On the Death Of Pdlcsmentioning
confidence: 99%
“…TXNIP/NLRP3 inflammasome play a key role in the pathogenesis of inflammation diseases and maintains redox balance in cells. Previous studies have shown that TXNIP exacerbates oxidative stress as well as increases inflammation in an NLRP3-dependent manner [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%